The role of the UN Organisation Mission in the Democratic Republic of the Congo (MonUC) with regard to democracy and human rights in the Democratic Republic of the Congo (DRC) - Bope, Mikobi Eugene (My University, 2011)
The Democratic Republic of the Congo (DRC) is a vast country in the Great Lakes region of Africa torn apart by repeated armed conflicts. As from September 1998, the conflict in the country attracted attention of the international community with the number of deaths estimated at around 3.3 million people. The 1998 armed conflict was the most complex in Africa, due to an intricate cluster of international and external factors, with up to nine states militarily involved inside the Congolese territory. These are grouped into two opposing sides, composed on the one side by the Kinshasa government with its Angolan, Namibian and Zimbabwean allies and on the other side a divided set of rebel groups composed of the Rassemblement Congolais pour la Démocratie (RCD) and the Mouvement pour la Libération du Congo (MLC) with their allies from Rwanda and Uganda. The United Nations (UN) Security Council is engaged in supporting international peace and security according to Chapters VI, VII and VIII of the UN Charter. The UN Organisation Mission in the Democratic Republic of the Congo (MONUC) is a special mission sanctioned by the UN as an effort to solving the political problems in the DRC in line with the adoption of resolutions 1355 (2001), 1376 (2001), 1417 (2002), 1445 (2002), 1493 (2003), 1565 (2004) and 1625 (2005) by the UN Security Council. It was established that MONUC confronted challenges of peace implementation, especially in the Eastern DRC. The aim of this research is to examine the role of MONUC with regard to the promotion of democracy and human rights in the DRC. Thus, from November 1999, MONUC started to operate in the Congolese peace process for the restoration of democracy, as well as the promotion of human rights in the country. This research report will demonstrate that MONUC contributed with strong political support towards the organisation of the 2006 national democratic elections. Meanwhile, the war was ended throughout the country, but human rights abuses continued to be committed in some Eastern areas up to date.
MA, International Relations, Faculty of Humanities, University of the Witwatersrand, 2011
Keywords: democracy; human rights; Democractic Republic of the Congo; DRC; UN; United Nations